A study on the acceptance level of rack housing in Malaysia - Ho, C. M.; Tan, Q. N.; Doh, S. I.; Omar, J.; Mohammed Al-Btoush, K. A. (Penerbit UMP, 2021)
Rack housing is one type of modular construction system which is flexible and poses a higher degree of mobility. However, the idea of rack housing is relatively new and there is no clear indication of how far is the acceptance of Malaysian citizen to this idea. Therefore, this study aims to identify the acceptance level of Malaysian towards rack housing and also serve as the basic reference for both government and private sector for the adoption fo rack house in Malaysia. In this study, the acceptance level among Malaysian factors of consumer decision to purchase rack housing and also the perspective of Malaysian especially middle income group is determined. A set of questionnaire was made by Google form which contain question about the major factor of acceptance of Malaysian citizen on rack housing with total of 208 questionnaires. The data collected from different group of Malaysian was analyzed by using Average Index (AI). The degree of importance was determined by the rating scales. The result obtained is that the acceptance level to purchase rack housing based on location, comfortability and management factors. From the result, the respondances agree to accept rack housing to implement and construct in Malaysia.